(untitled) (LEARNing Landscapes, 2022)
Employing applied theatre techniques of playbuilding, research-grounded scene development, and facilitated workshops has the potential to provide transformative learning. The He-ART-istic Journeys-Heart DIS-ease play is one example that invites learners to experience (living with heart disease). This aesthetic encounter creates a reflective space that embraces the uncertainty of (un)knowing-necessary to participate in relearning. Engaging in Mirror Theatre’s method of dialogic exploration, we share two scenes that demonstrate the pedagogical potential and creative process for transformative teaching purposes.